Análise da responsividade ao tratamento de pacientes com Hipertensão Arterial Sistêmica atendidos no ambulatório de cardiologia da Universidade Federal do Pará - WOSNY, Cristiane (2022)
Introduction: Hypertension is, today, seen as a disease inserted in a context more than just the one resulting from blood pressure levels. Objective: Watch the cardiovascular risk and the treatment outcome of the hypertensive patients evaluated at the Cardiology Ambulatory of a university hospital in Pará. Methods: Observational, descriptive and transversal study of all the hypertensive patients, having at least three earlier appointments, using or not anti-hypertensive drugs, in that ambulatory, during the month from January to march of 2005. Information was collected regarding to demographic factors, cardiovascular risk factors, target organs damage, blood pressure levels and treatment. Results: The average of age found was 56,3 years old, the majority of the patients were of the female gender (60,8%) and brown race (75,4%). Dyslipidemia was found in 59,2% of the individuals and diabetes in 12,3%, 8,5% declared themselves as current smokers and 46,2% as former smokers, 67,7% did not have regular physical activity. Overweight was a condition encountered in 44,6% and obesity in 30,7% of the patients. A positive family history to hypertension was found in 67,7%. In 18,5% of the patients was found left ventricular hypertrophy, in 14,6% heart failure, 10% had kidney disorders and 7,7% had a history of cerebrovascular disorders. In 33,9% of the patients, the blood pressure was under 140/90mmHg at the moment of the interview. The ACEI was being used by 53,8% of the patients. Conclusion: The hypertensive patients going to the Cardiology Ambulatory of UFPA have a high cardiovascular risk profile and a poor blood pressure control. More efforts are necessary to keep the blood pressure under control and decrease the morbidity and mortality of the cardiovascular disease.